Diffuse Venous Malformation of Perineum - Khan, Md Saif Ullah; Islam, Md Faridul; Adhikary, Dipal Krishna (University Heart Journal, 2018)
Abstract not available University Heart Journal Vol. 13, No. 1, January 2017; 36-37